The Values ​​of Islamic Education in Aidh AL-Qarni's La Tahzan Book and Its Relevance: Nilai-Nilai Pendidikan Islam dalam Buku La Tahzan Karya Aidh AL-Qarni dan Relevansinya - Nanda Wulan Hidayah; Ainun Nadlif (Universitas Muhammadiyah Sidoarjo, 2021)
This article aims to add scientific references about the values ​​of Islamic education in the book La Tahzan by Aidh Al-Qarni and its relevance, so that later if anyone is looking for references about the values ​​of Islamic education in the book La Tahzan, they can multiply so that it can make it easier for readers. . The research approach used is library research, the data obtained from the literature with a theoretical and philosophical approach. The results of the study found that the values ​​of Islamic education in La Tahzan's book contained the values ​​of Islamic education in faith, morality, worship and national values.